Kinetic study on the effect of substrate and micronutrient inhibition during anaerobic fermentation of biohydrogen - Engliman, Nurul Sakinah; Abdul Aziz, Ainul Husna; Mansor, Mariatul Fadzillah; Abdul, Peer Mohamed; Md Jahim, Jamaliah; Jamali, Nur Syakina (IJCSRR, 2022)
There are several factors that influence the production of biohydrogen by dark fermentation including inoculum seeds, type, and concentration of substrate, pH, temperature, presence of micronutrients and reactor configuration. Previous research has proven that the concentration of substrate and the presence of micronutrients will influence the yield and productivity of biohydrogen production. However, improvement of yield and productivity of the process can only be achieved once the system is under the optimum amount of substrate and micronutrients. Therefore, the best way to determine the effect of substrate concentration and presence of micronutrients is through kinetic study that was done using the Monod model along with the Andrews model. Besides that, the substrate inhibition effect also will be evaluated to determine the maximum substrate that needs to be supplied for maximum hydrogen production and thus supplied the information for economic feasibility for the fermentation process. In the meantime, the inhibition effect of adding the iron nanoparticles also had been evaluated to understand the interaction effect between iron nanoparticles and bacteria in terms of catabolism reaction. It was found that increasing the substrate concentration by more than 10 g/l will cause inhibition to the system, which will slow down the reaction process and reduce the production of hydrogen. While the presence of iron NPs more than its optimum value (200 mg/l) will inhibit bacterial growth and hence, affect hydrogen production. For both cases, when the inhibition occurred at the respective concentration, it was found that the metabolic pathway was shifted to produce more hydrogen-consuming metabolites such as propionate acid, and thus, dropped hydrogen production.